Kontribusi konsep diri terhadap motivasi belajar siswa di sekolah - Heru Sriyono (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
Potential learners that must be built up not merely deals with the issue of intelligence and skills, but involves all forms of personality and self-concept and learning motivation. The purpose of this study is to determine the contribution given by self-concept variable to student's motivation variable. This research is a correlational research involving 40 students in SMA N 64 Jakarta. Data analysis was performed by simple linear regression technique. The findings of this research is that there is a significant relationship between self-concept and student learning motivation. The contribution of self-concept to student's learning motivation is still relatively small in this research, that is 6%.